Position sensitive resonant Schottky cavities for heavy ion storage rings - Dmytriiev, Dmytro; Sanjari, Mohammad Shahab; Litvinov, Yuri A.; Stöhlker, Thomas (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2020)
Resonant Schottky pick-up cavities are sensitive beam monitors. They are indispensable for the beam diagnostics in storage rings. Apart from their applications in the measurements of beam parameters, they can be used in nondestructive in-ring decay studies of radioactive ion beams. In addition, position sensitive Schottky pick-up cavities enhance precision in the isochronous mass measurement technique. The goal of this work is to construct and test such a position sensitive cavity (e.g. Schottky detector) based on previous theoretical calculations and simulations. These cavities will allow measurement of position using the monopole mode using a non-circular(elliptic) geometry. This information can be further analyzed to increase the performance in isochronous mass spectrometry. A brief description of the detector system from elliptical and cylindrical cavities is described in this work.